Night work, long work weeks, and risk of accidental injuries. A register-based study - Larsen, Ann Dyreborg; Hannerz, Harald; Møller, Simone V.; Dyreborg, Johnny; Bonde, Jens Peter; Hansen, Johnni; Kolstad, Henrik A.; Hansen, Åse Marie; Garde, Anne Helene (Scandinavian Journal of Work, Environment & Health, 2017)
' ' OBJECTIVES ': 'The aims of this study were to (i) investigate the association between night work or long work weeks and the risk of accidental injuries and (ii) test if the association is affected by age, sex or socioeconomic status. ' ' METHODS ': 'The study population was drawn from the Danish version of the European Labour Force Survey from 1999–2013. The current study was based on 150 438 participants (53% men and 47% women). Data on accidental injuries were obtained at individual level from national health registers. We included all 20–59-year-old employees working ≥32 hours a week at the time of the interview. We used Poisson regression to estimate the relative rates (RR) of accidental injuries as a function of night work or long work weeks (>40 hours per week) adjusted for year of interview, sex, age, socioeconomic status (SES), industry, and weekly working hours or night work. Age, sex and SES were included as two-way interactions. ' ' RESULTS ': 'We observed 23 495 cases of accidental injuries based on 273 700 person years at risk. Exposure to night work was statistically significantly associated with accidental injuries (RR 1.11, 99% CI 1.06–1.17) compared to participants with no recent night work. No associations were found between long work weeks (>40 hours) and accidental injuries. ' ' CONCLUSION ': 'We found a modest increased risk of accidental injuries when reporting night work. No associations between long work weeks and risk of accidental injuries were observed. Age, sex and SES showed no trends when included as two-way interactions.